Research and analysis of least square method identification of children's movement based on running and mountain climbing. Issue 3 (October 2020) - Zhao, Huoping; Wang, Dong; Li, Dahu; Sun, Kang; Zhang, Wanjun; Gou, Xiaoping
Abstract: In view of the difference of safe heart rate during exercise and fitness, this paper studies the suitable heart rate of children running and climbing in different physique, so as to provide scientific and effective exercise for children. In this paper, a least square method is proposed to identify children's movement based on running and climbing. The least square method identification system of children's movement based on running and mountain climbing is established. Finally, through the MATLAB simulation analysis, the results show that the discrete identification method is suitable for children's safe heart rate and physical fitness, and the simulation results verify the feasibility and effectiveness of the least square identification method.